Case 3715: Punctuated avian species-group names as abbreviations in the zoological appendix of Linnaeus' Mantissa Plantarum Altera, 1771: proposed conservation of leucorynchus and mascarinus as justified emendations of their respectively punctuated original spellings as Lanius leucoryn. and Psittacus mascarin. - Schodde, Richard; Dowsett, Robert J; Bock, Walter J (Bulletin of Zoological Nomenclature, 2017)
The purpose of this application, under Articles 78.1, 80.2. and 81.1 of the Code, is to conserve the in-use spellings leucorynchus Linnaeus, 1771 and mascarinus Linnaeus, 1771 as respective justified emendations of the specific names for the woodswallow, Artamus leucorynchus (Linnaeus, 1771), type species of the avian genus Artamus (Artamidae), and the parrot, Mascarinus mascarinus (Linnaeus, 1771), type species of the avian genus Mascarinus (Psittacidae). In an Appendix for animal species in his Mantissa Plantarum Altera (1771), Linnaeus originally published these names as “mascarin.” and “leucoryn.” in the binomina Lanius leucoryn. and Psittacus mascarin., with punctuation marks. Because of punctuation, they have been treated as abbreviated and spelled out almost universally since the late 18th century. Their spelling-out is now being challenged by reinterpretation and reintroduction of mascarin and leucoryn as unabbreviated. Evidence from the formatting and punctuation of species names in the Mantissa Plantarum Altera is presented to show that leucoryn. and mascarin. are, in fact, abbreviated; and the ruling of Official Correction 82 of the Commission in an associated case is cited in support. In the interests of nomenclatural stability, and to accord with the ruling of Official Correction 82, it is proposed that leucoryn. Linnaeus, 1771 and mascarin. Linnaeus, 1771 be determined as incorrect original spellings, and that all spelling-outs of leucoryn. and mascarin. other than leucorynchus and mascarinus respectively be ruled as unjustified emendations. An appended table lists all 20 punctuated animal names in the Mantissa Plantarum Altera, recording those that are abbreviated and those that are not, and identifying the nominal species to which they apply today.
Keywords: Nomenclature; taxonomy; Aves; Artamus leucorhynchus; Lanius leucoryn.; Mascarinus mascarinus; Psittacus mascarin.; Linnaeus; Mantissa Plantarum; Australasia; Indonesia; Mascarene Islands; abbreviation